Polymer composition containing cellulose nanocrystals derived from wheat bran, and molded articles and fibers thereof

The use of cellulose nanocrystals derived from wheat bran in polymer compositions addresses the limitations of existing cellulose fiber-based materials by enhancing strength and transparency, resulting in superior films, sheets, and fibers.

JP7660809B2Active Publication Date: 2025-04-14SHINSHU UNIVERSITY +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021054598
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-04-14
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

Existing polymer compositions containing cellulose fibers as fillers lack satisfactory strength and transparency, making it difficult to produce films, sheets, or fibers with sufficient properties.

Method used

A polymer composition incorporating cellulose nanocrystals derived from wheat bran, which are chemically defibrated and used as fillers in various polymer resins, enhancing the physical properties of the resulting molded products and fibers.

Benefits of technology

The polymer composition achieves improved tensile strength, elastic modulus, and transparency, enabling the production of high-strength, transparent films, sheets, and fibers that surpass the performance of similar products made from cotton-derived nanocellulose.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660809000004
    Figure 0007660809000004
  • Figure 0007660809000005
    Figure 0007660809000005
  • Figure 0007660809000006
    Figure 0007660809000006
Patent Text Reader

Abstract

To provide a polymer composition which has improved strength and transparency and contains a cellulose fiber as a filler and a molded article of the same, and a fiber of which the raw material is readily available, and that uses nanocelluloses excellent in strength and transparency.SOLUTION: There are provided a polymer composition that contains a wheat bran-derived cellulose nanocrystal, wherein preferably, the wheat bran-derived cellulose nanocrystal has an average size of 2-100 nm, an average length of 100-2,000 nm, and a carboxyl group of 30-2,000 μmol / g; a molded article of the same such as a sheet or a film; and a fiber containing the wheat bran-derived cellulose nanocrystal.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer composition containing wheat bran-derived cellulose nanocrystals, and its molded article and fiber. Specifically, the polymer composition of the present invention is a composition in which wheat bran-derived cellulose nanocrystals produced by chemically defibrating wheat bran are contained as a filler in various polymer resin substrates, and it shows excellent physical properties in terms of tensile strength, elastic modulus, transparency, etc., and is expected to be processed into various molded articles, including sheets and films, and used in a wide range of fields. In addition, the fiber of the present invention is produced by spinning from a spinning solution containing wheat bran-derived cellulose nanocrystals. [Background technology]

[0002] A composite material in which nano-sized particles of filler (nanofiller) are dispersed in a polymer material as the base material (parent material) is called a nanocomposite. Nanocomposites are used in various technical fields because their formation dramatically improves various physical properties such as tensile strength, elastic modulus, and heat distortion temperature, and development to achieve even higher functionality is ongoing.

[0003] In the past, inorganic materials were mainly used as nanofillers, but in recent years, nanocellulose obtained from cellulose, which has long been used as a fiber material, has also been used as a nanofiller. When nanocellulose, a fibrous material obtained by physically or chemically defibrating plant-derived fibers, is used as a filler, a lighter polymer composition can be obtained compared to inorganic fillers. Nanocellulose is also biodegradable, which is an advantage in terms of environmental impact.

[0004] Heretofore, polymer compositions containing physically or chemically treated plant biomass materials as a filler have been known. Patent Document 1 describes that a cellulose-containing solid obtained by heat-treating plant biomass in a mixed solvent of water and an aliphatic alcohol having 4 to 8 carbon atoms has good mixability with thermoplastic resins and improves the thermal stability of the resin. Patent Document 2 describes that a composition consisting of cellulose fibers obtained from plant raw materials and a polyolefin having specific properties, that is, a polyalkene having a carboxy group, has high dispersibility in olefin resins.

[0005] Patent Documents 3 and 4 describe sheet- or film-like compositions containing an impregnated mixture obtained by impregnating porous powder obtained by pulverizing porous herbaceous biomass such as wheat bran with an inorganic filler, and a polyolefin resin.

[0006] Patent Document 5 discloses a resin composition that contains cellulose fibers (pulverized after TEMPO oxidation treatment) made from natural fibers and a natural and / or synthetic resin emulsion and can form a dry coating with high elasticity. It describes that the composition contains cellulose fibers with an average fiber diameter of 200 nm or less and that the carboxyl group content of the cellulose is 0.1 to 2 mmol / g. Patent Document 6 describes a thermoplastic resin composition containing 2 to 30 mass % of defibrated material obtained by physically defibrating bran.

[0007] Fibers using nanocellulose are also known. Patent Document 7 discloses cellulose fibers obtained by a method of spinning fibers containing cellulose nanofibrils by extruding a suspension of cellulose nanofibrils extracted from a cellulose-rich material such as wood through a spinneret. Patent Document 8 discloses a high-strength PVA-based composite fiber that can be produced by extruding a spinning solution in which cellulose nanofibers are added to PVA (polyvinyl alcohol) through a nozzle into cooled methanol to obtain a spun gel-like raw yarn, and then stretching this spun gel-like raw yarn. Patent Document 9 describes fibers obtained through a process in which a solution of microcrystalline cellulose dissolved in N,N-dimethylformamide or the like is discharged from a nozzle into methanol and stretched.

[0008] On the other hand, cellulose nanocrystals derived from wheat bran have been reported as an example of plant-derived nanocellulose. Non-Patent Document 1 reports that wheat bran cellulose is purified by subjecting wheat bran to defatted, destarched, and deproteinized treatments, and then the purified wheat bran cellulose is subjected to acid hydrolysis to obtain cellulose nanocrystals. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2017-002206 A [Patent Document 2] JP 2017-141323 A [Patent Document 3] JP 2014-162923 A [Patent Document 4] JP 2015-151550 A [Patent Document 5] JP 2009-197122 A [Patent Document 6] JP 2019-172876 A [Patent Document 7] Special Publication No. 2013-525618 [Patent Document 8] JP 2011-208293 A [Patent Document 9] JP 2009-203467 A [Non-patent literature]

[0010] [Non-Patent Document 1] International Journal of Biological Macromolecules, 140(2019), 225-233 Cellulose nanocrystals prepared from wheat bran: Characterization and cytotoxicity assessment Summary of the Invention [Problem to be solved by the invention]

[0011] Although various improvements have been made to polymer compositions containing cellulose fibers as a filler, they are still not satisfactory in terms of strength and transparency, and it has been difficult to obtain films, sheets, or fibers with sufficient strength and transparency, so a polymer composition with further improved strength and transparency has been required. In addition, as cellulose fibers, nanocellulose derived from cotton imported from overseas has been mainly used so far, and there has been a demand for fibers using nanocelluloses that can be easily obtained in large quantities domestically and have the same or better performance in terms of strength and transparency. [Means for solving the problem]

[0012] The above problems can be solved by the following polymer composition and molded article thereof, as well as a fiber comprising wheat bran-derived cellulose nanocrystals. 1. A polymer composition containing cellulose nanocrystals derived from wheat bran. 2. The polymer composition according to claim 1, wherein the polymer is a thermoplastic resin. 3. The polymer composition according to 1 or 2, wherein the wheat bran-derived cellulose nanocrystals have an average diameter of 2 to 100 nm, an average length of 100 to 2000 nm, and a carboxy group content of 30 to 2000 μmol / g. 4. The composition of 1. to 3., which contains 1 to 20% by mass of cellulose nanocrystals derived from wheat bran. The polymer composition according to any one of the preceding claims. 5. A molded article of the polymer composition according to any one of 1. to 4. 6. The molded article according to 5., wherein the molded article is a sheet or film. 7. (1) A process for preparing wheat bran-derived cellulose nanocrystals by subjecting wheat bran to sulfuric acid hydrolysis; (2) mixing wheat bran-derived cellulose nanocrystals with a polymer; and (3) molding the resulting mixture; A method for producing a molded article according to 5. or 6., comprising: 8. Fiber containing cellulose nanocrystals derived from wheat bran. 9. The fiber according to 8., in which the wheat bran-derived cellulose nanocrystals have an average diameter of 2 to 100 nm, an average length of 100 to 2000 nm, and a carboxyl group content of 30 to 2000 μmol / g. 10. The fiber according to 8. or 9., which contains other polymers in addition to wheat bran-derived cellulose nanocrystals. 11. The fiber according to claim 10, wherein the other polymer is one or more selected from chitin-derived nanocellulose from crab shells, nanocellulose derived from sea squirts, and nanocellulose derived from cotton. 12. The fiber according to 10, wherein the other polymer is one or more selected from polyvinyl alcohol and nylon. 13. (1) A process for preparing wheat bran-derived cellulose nanocrystals by subjecting wheat bran to sulfuric acid hydrolysis; (2) dispersing wheat bran-derived cellulose nanocrystals in a solvent; and (3) spinning the resulting mixture; Including, A method for producing a fiber according to any one of 8. to 12. 14. Dispersing wheat bran-derived cellulose nanocrystals in a solvent to prepare a spinning dope; and forming fibers from the resulting spinning dope; 14. The method according to claim 13, wherein the spinning dope contains 1 to 10 mass % of wheat bran-derived cellulose nanocrystals. 15. A process of dispersing and mixing wheat bran-derived cellulose nanocrystals and a polymer in a solvent to prepare a spinning dope; and forming fibers from the resulting spinning dope; 15. The method according to claim 14, wherein the spinning dope contains 1 to 10 mass % of wheat bran-derived cellulose nanocrystals. Effect of the Invention

[0013] Nanocomposites can be produced by a simple method from the polymer composition containing the wheat bran-derived cellulose nanocrystals of the present invention, and various molded products that are lightweight and safe because they contain wheat bran-derived cellulose nanocrystals as a filler, as well as excellent in strength and transparency, can be obtained. For example, films, sheets, and fibers that are strong and highly transparent can be produced from the polymer composition containing the wheat bran-derived cellulose nanocrystals of the present invention.

[0014] In addition, in the present invention, the fibers produced by a known spinning method from a spinning dope containing wheat bran-derived cellulose nanocrystals are lightweight, flexible, and have excellent strength and transparency, so that it is possible to obtain fibers that are light, strong, and have excellent dyeability. [Brief description of the drawings]

[0015] [Figure 1] Appearance of PVA nanocomposite film containing wheat bran-derived cellulose nanocrystals (cellulose nanocrystal content: 5%). [Diagram 2] Light transmittance of various nanocellulose-containing PVA nanocomposite films (converted to a thickness of 50 μm) (WBM is derived from wheat bran, Cotton is derived from cotton) [Diagram 3] Appearance (left) and optical microscope image (right) of cellulose nanocrystal fibers derived from wheat bran DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The method for producing the polymer composition and fiber containing wheat bran-derived cellulose nanocrystals of the present invention will be described below.

[0017] (Cellulose Nanocrystals) Nanocellulose is cellulose microfibrils obtained by physically and / or chemically defibrating cellulosic raw materials, and is also called cellulose nanofiber or cellulose nanocrystal. Cellulose nanofibers are generally produced by mechanical fiberization methods and have an average diameter of 4 to 100 nm, an average length of 5 μm or more, and a high aspect ratio. Cellulose nanocrystals, also called cellulose nanowhiskers, are generally needle- or whisker-like crystals with an average diameter of 3 to 50 nm and an average length of about 100 to 500 nm, produced by an acid hydrolysis method. Of the acid hydrolysis methods for producing cellulose nanocrystals, a method in which hydrolysis is carried out using sulfuric acid is considered to be particularly preferred.

[0018] (Wheat bran) Wheat bran is the skin of wheat seeds. Wheat bran is generally produced by separating it from the endosperm and germ of wheat seeds during the milling process of wheat flour. However, since it is difficult to completely separate the skin from the endosperm and germ during the normal milling process, wheat bran that is normally distributed may contain the endosperm and germ. In addition, wheat bran may be either the bran that is generated during the milling process or defatted bran from which fats and oils have been removed. The wheat bran used in the present invention may be the skin separated from the wheat seeds, but may also be the above-mentioned normally distributed wheat bran or defatted bran. Various types of wheat bran are commercially available from flour milling companies, and these commercially available wheat brans can be used in the present invention.

[0019] (Cellulose nanocrystals derived from wheat bran) The wheat bran-derived cellulose nanocrystals used in the present invention can be prepared by using cellulose obtained by purifying the above-mentioned raw material wheat bran and subjecting it to acid hydrolysis treatment.

[0020] The processes for obtaining refined cellulose from raw wheat bran include degreasing and / or delignification and / or deproteinization.

[0021] In the degreasing process, the raw wheat bran is mixed with a solvent, and the raw wheat bran is brought into contact with the solvent while stirring the mixture as necessary. The type of solvent is not particularly limited, but examples include methanol, ethanol, benzene, toluene, xylene, acetone, chloroform, etc. After contact with the solvent, the bran is air-dried to obtain defatted bran.

[0022] The defatted wheat bran is preferably then subjected to a delignification (bleaching) process. In the bleaching process, the defatted wheat bran is added with a bleaching solution and heated under reflux. The type of the bleaching solution is not particularly limited, but examples thereof include a mixture of water, sodium hydroxide, acetic acid, and sodium chlorite. After the heating and refluxing process in the bleaching solution, the bran is washed by repeated centrifugation and washing with water to obtain bleached wheat bran.

[0023] It is further preferable to then carry out a deproteinization treatment. In the deproteinization process, the bleached wheat bran is brought into contact with an alkaline solution. The type of alkaline solution is not particularly limited, but examples include aqueous solutions of potassium hydroxide, sodium hydroxide, barium hydroxide, etc. After contact with the alkaline solution, the bran is repeatedly centrifuged and washed with water to obtain deproteinized wheat bran (refined wheat bran). Most preferably, the delignification and deproteinization processes are repeated until the sample is pure white.

[0024] The refined wheat bran is then subjected to an acid hydrolysis treatment. In the acid hydrolysis treatment, an acid solution is added to the refined wheat bran and stirred while heating. The type of acid solution is not particularly limited, but examples include aqueous solutions of sulfuric acid, hydrochloric acid, hydrobromic acid, etc. After the heating and stirring treatment, the mixture is repeatedly centrifuged and washed with water to obtain a cloudy supernatant, which is then collected and dialyzed to neutralize it to obtain cellulose nanocrystals.

[0025] The wheat bran-derived cellulose nanocrystals used in the present invention preferably have an average diameter of 2 to 100 nm, an average length of 100 to 2000 nm, and a carboxyl group content of the surface functional groups of 30 to 2000 μmol / g.

[0026] (polymer) The polymer used in the production of the polymer composition of the present invention is not particularly limited, and both thermoplastic resins and thermosetting resins can be used. The polymer may be used alone or in combination of two or more. Among these, thermoplastic resins are particularly preferred. The thermoplastic resin used in the present invention is not particularly limited, but examples thereof include polyvinyl alcohol resins, polycarbonate resins, styrene resins, polystyrene resins, polyethylene resins, polypropylene resins, polyacrylic resins, polyvinyl chloride resins, cellulose acetate resins, polyamide resins, and copolymers of these with other monomers. Among these, polyvinyl alcohol resins are particularly preferred.

[0027] The polymer composition of the present invention can be produced by mixing the above-mentioned wheat bran-derived cellulose nanocrystals and a polymer. Various molded articles can then be produced by molding the resulting mixture. In the production of the polymer composition of the present invention, the procedure for mixing the wheat bran-derived cellulose nanocrystals and the polymer and molding the mixture is not particularly limited as long as it is a procedure that can obtain a molded product of a uniform mixture of bran-derived nanocellulose and a polymer, and known means used in polymer molding, such as cast molding, extrusion molding, injection molding, blow molding, and spinning for fiber production, can be appropriately adopted depending on the shape, size, etc. of the desired molded article.

[0028] A preferred example of a procedure for mixing wheat bran-derived cellulose nanocrystals with a polymer according to the present invention and molding the mixture includes heating and melting the polymer, adding to it a dispersion of the above-mentioned wheat bran-derived cellulose nanocrystals dispersed in a medium such as water, methanol, ethanol, or acetone, mixing, drying the resulting mixture to remove the liquid components of the dispersion, and then molding the mixture.

[0029] From the viewpoints of plasticity and strength, the blending ratio (dry matter equivalent) of wheat bran-derived cellulose nanocrystals to polymer in the polymer composition of the present invention is preferably 1 to 20 mass% of wheat bran-derived cellulose nanocrystals in the solid content (resin + nanocellulose) of the polymer composition, more preferably 1 to 15 mass%, and even more preferably 1 to 10 mass%.

[0030] The polymer composition of the present invention may contain, in addition to the wheat bran-derived cellulose nanocrystals and polymer described above, other additives that are typically used in polymer compositions.

[0031] Examples of the other additives include inorganic fillers such as silica powder, alumina powder, glass powder, glass fiber, glass flakes, mica, talc, calcium carbonate, alumina, hydrated alumina, boron nitride, aluminum nitride, silicon nitride, silicon carbide, titanium nitride, zinc oxide, tungsten carbide, and magnesium oxide; organic fillers such as carbon fiber, aramid fiber, paper powder, cellulose fiber, cellulose powder, rice husk powder, fruit shells and nuts powder, chitin powder, and starch; compatibilizers; surfactants; stabilizers; ultraviolet absorbers; flame retardants; antistatic agents; defoamers; release agents; antioxidants; plasticizers; dyes; and thermosetting resins. The other additives may be added when mixing the wheat bran-derived cellulose nanocrystals with the polymer, or may be added to either the wheat bran-derived cellulose nanocrystals or the polymer before mixing.

[0032] (fiber) The fibers containing the wheat bran-derived cellulose nanocrystals of the present invention can be produced by mixing the above-mentioned wheat bran-derived cellulose nanocrystals in a solvent to obtain a suspension in which the wheat bran-derived cellulose nanocrystals are uniformly dispersed, using this as a spinning solution (dope), and extruding this through a nozzle or the like into a coagulation bath to form a spun gel-like raw yarn, which is then dried. The content of the wheat bran-derived cellulose nanocrystals in the spinning solution is preferably 1 to 10% by mass.

[0033] The solvent for the spinning solution is not particularly limited as long as it can easily dissolve the polymer and disperse the wheat bran-derived cellulose nanocrystals sufficiently, and examples of the solvent include water, dimethyl sulfoxide, and a mixture of water and dimethyl sulfoxide. Of these, water is preferably used.

[0034] Furthermore, by combining other polymers in the solvent, such as polyvinyl alcohol, nylon 6, polystyrene, polyethylene, and polyester, or nanocrystals of different origins other than wheat bran-derived cellulose nanocrystals, such as chitin nanocrystals derived from crab shells, cellulose nanocrystals derived from sea squirts, and cellulose nanocrystals derived from cotton, a variety of nanocomposite fibers can be produced.

[0035] For example, fibers using polyvinyl alcohol as the other polymer can be produced according to the method described in Patent Document 8 (JP Patent Publication 2011-208293 A), by using the above-mentioned wheat bran-derived cellulose nanocrystals instead of the cellulose nanofibers of Patent Document 8.

[0036] The spinning step can be carried out by a gel spinning method. As the gel spinning method for converting the spinning solution from a sol to a gel, any of wet extrusion gel spinning in which the spinning solution is extruded from a nozzle into a coagulation bath containing a solvent such as methanol, and dry gel spinning in which a cooling gas is blown onto the solution can be used, but extrusion gel spinning is preferred. The coagulation bath used in wet extrusion gel spinning is not particularly limited, but may be, for example, a mixture of water and methanol. For example, a 70% aqueous methanol solution containing 0.1% CaCl2 is a particularly preferred coagulation bath.

[0037] After spinning, a desolvation and drying process is carried out. The spun gel-like raw yarn is immersed in an organic solvent to remove the solvent, and then air-dried or dried under reduced pressure. Note that the desolvation process may be omitted and the raw yarn may be air-dried or dried under reduced pressure. Drying under reduced pressure may also be performed. EXAMPLES

[0038] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0039] Example 1 (Preparation of cellulose nanocrystals from wheat bran) (Degreasing) 100 g of wheat bran (Wheat Bran M, Nisshin Pharma) was subjected to Soxhlet extraction overnight using an ethanol / benzene mixture (2:1, 1.5 L), and then air-dried to obtain defatted bran. (Delignification) A bleaching solution (500 mL of water, 6.75 g of NaOH, 18.75 mL of acetic acid, and 4.25 g of sodium chlorite) was added to 50 g of defatted bran, and the mixture was heated to reflux at 80°C for 7 hours for bleaching. The bleached solid was repeatedly washed with water using a centrifuge to obtain a wet solid. (Deproteinization) 50 g of the delignified sample was stirred overnight in 5% KOH aqueous solution (1 L), and then repeatedly washed with 5% KOH and then with water using a centrifuge. After deproteinization, the sample was further subjected to delignification treatment to make it pure white, and refined wheat bran was obtained.

[0040] (Preparation of cellulose nanocrystals from wheat bran by acid hydrolysis) 2 g of purified wheat bran was added to 65% sulfuric acid (60 mL), stirred uniformly, and then stirred in a water bath at 70 °C for 10 minutes. After the reaction was completed, the mixture was diluted 3 times with water and repeatedly washed with water using centrifugation. When a cloudy white supernatant was obtained, it was collected and dialyzed to neutralize, and an aqueous suspension of wheat bran-derived cellulose nanocrystals was obtained.

[0041] (Quantitative determination of surface functional groups by conductometric titration) Using a conductivity meter (Seven Go Duo-SG78, conductivity electrode InLab 751-4mm, Mettler Toledo), an aqueous suspension containing 150 mg of wheat bran-derived cellulose nanocrystals was titrated with 0.01 M NaOH solution to track the change in conductivity. The amount of NaOH up to the first bending point corresponds to strong acidic groups (sulfate ester groups), and the amount of NaOH between the first and second bending points corresponds to weak acidic groups (carboxy groups), and was converted into the amount of surface functional groups of the cellulose nanocrystals.

[0042] The amount of surface functional groups determined by the above-mentioned conductometric titration is shown in Table 1. For comparison, the amount of functional groups in cellulose nanocrystals obtained by acid hydrolysis of cotton and wood pulp under almost the same conditions is also shown.

[0043] [Table 1]

[0044] From Table 1, it can be seen that the amount of carboxyl groups present on the surface of wheat bran-derived cellulose nanocrystals is extremely large compared to those derived from wood pulp or cotton (12.3 times that of wood pulp-derived, whereas cotton-derived has almost no carboxyl groups). The amount of sulfate ester groups introduced by sulfuric acid hydrolysis is also large in wheat bran-derived cellulose nanocrystals compared to those derived from wood pulp or cotton (4.4 times that of wood pulp-derived, 2.6 times that of cotton).

[0045] (Particle morphology observation) Using a transmission electron microscope (TEM, FEM-2100, JOEL), the morphology of cellulose nanocrystal particles derived from wheat bran was observed without staining at a voltage of 80 kV, and the average diameter and length were measured, yielding an average diameter of 27.5 ± 3.5 nm and an average length of approximately 300 to 1000 nm.

[0046] Example 2 (Preparation of Nanocomposite Films) Polyvinyl alcohol resin (PVA) with a saponification degree of 98% and a polymerization degree of 1800 was purchased from Wako Pure Chemical Industries, Ltd. A 10 wt% aqueous solution of PVA (prepared by dissolving PVA in heated deionized water) and a 2 wt% suspension of wheat bran-derived cellulose nanocrystals were prepared and mixed so that the ratios of wheat bran-derived cellulose nanocrystals / (PVA + wheat bran-derived cellulose nanocrystals) were 2.5%, 5%, and 10%. The mixture was cast onto a Teflon petri dish and dried in a desiccator containing diphosphorus pentoxide until solidified, yielding a nanocomposite film. As a control, cotton-derived nanocellulose with a TEMPO-oxidized surface and carboxyl groups introduced was used. For the following physical property measurements, the film was cut into a rectangular test piece having a width of 5 mm and a length of 40 mm.

[0047] (Tensile test) The mechanical properties were measured using a tensile testing machine (EZ-S, Shimadzu Corporation) with a load cell of 50 N, grip distance of 20 mm, and tensile speed of 4 mm / min to obtain Young's modulus and breaking strength.

[0048] (transparency) The transparency of the film was directly measured using an ultraviolet-visible light absorptiometer (UV-2700, Shimadzu Corporation) and converted into the transmittance of a film with a thickness of 50 μm, assuming that the Lambert-Beer law holds true.

[0049] (result) The appearance of the obtained wheat bran-derived cellulose nanocrystal-containing film is shown in Figure 1. A film with extremely high transparency was obtained. It was more transparent to the naked eye than a cotton-derived nanocellulose-containing film with the same nanocellulose content.

[0050] The results of measuring the transmittance of ultraviolet and visible light are shown in Figure 2. Here again, it was clearly shown that the wheat bran-derived cellulose nanocrystal-containing film of the present invention has high transparency. In a relative comparison between the wheat bran-derived cellulose nanocrystal-containing films, the film with a wheat bran-derived cellulose nanocrystal content of 5% had the lowest transparency, and the films with a content of 2.5% and 10% had higher transparency.

[0051] The mechanical properties of the films are shown in Table 2. At a content of 2.5%, there was no difference in Young's modulus between the wheat bran-derived cellulose nanocrystal-containing film (WBM) and the cotton-derived cellulose nanocrystal-containing film (Cotton). For the breaking strength, when the content was 2.5%, there was a tendency for the products to vary widely, but at all blend ratios, the film containing wheat bran-derived cellulose nanocrystals outperformed the film containing cotton-derived cellulose nanocrystals. Based on the above, by using wheat bran-derived cellulose nanocrystals as a reinforcing filler, it is possible to prepare nanocomposite films with higher mechanical properties and transparency than those of cotton-derived cellulose nanocrystals.

[0052] [Table 2]

[0053] Example 3 (Wet spinning) Fibers composed of 100% crystals were prepared by wet spinning nanocellulose. The aqueous suspension of bran-derived nanocellulose prepared above was concentrated to about 10% by osmotic concentration (a method in which the aqueous suspension is sealed in a dialysis tube, then immersed in a 10% aqueous solution of polyethylene glycol 20,000, and only the water is expelled from the tube by osmotic pressure to concentrate), and then diluted to 4.1% with deionized water to prepare a spinning solution (dope). This dope was sealed in a syringe and injected through a 23G needle into a coagulation bath (70% methanol containing 0.1% CaCl2) at an injection rate of 0.10 mL / min. The gel-like fibers were pulled up and collected, then air-dried to obtain fibers. For comparison, cotton-derived nanocellulose fibers (dope concentration 13%) and sea squirt-derived nanocellulose fibers (dope concentration 8%) were prepared.

[0054] When the fibers obtained by wet spinning were air-dried, a lightweight, flexible, and transparent fiber was obtained, as shown in Figure 3.

[0055] The prepared fibers were observed under an optical microscope and tensile tests were performed to measure the Young's modulus and breaking strength. The Young's modulus and breaking strength of the fibers prepared from various nanocellulose sources, including the wheat-derived nanocellulose of the present invention, are shown in Table 3.

[0056] [Table 3]

[0057] Despite the lower dope concentration compared to cotton fibers, bran-derived nanocellulose fibers showed mechanical properties comparable to or even exceeding those of cotton fibers, which are known to be highly crystalline cellulose (the physical properties of cotton fibers are the highest among various spinning conditions, with typical values ​​being Young's modulus of 5-10 GPa and breaking strength of about 30-50 MPa at a dope concentration of 10-13%). The values ​​shown are comparable to those of sea squirt-derived nanocellulose fibers, which have the highest degree of crystallinity among natural celluloses. Considering that sea squirt-derived nanocellulose requires a dope of 8 wt%, the higher mechanical properties are achieved at a lower dope concentration, making it possible to produce a lighter fiber.

[0058] (Tensile test) The mechanical properties were measured using a tensile testing machine (EZ-S, Shimadzu Corporation) with a load cell of 5N, grip distance of 20mm, and strain rate of 2mm / min to obtain Young's modulus and breaking strength.

[0059] Furthermore, in the method described in Examples 1 to 5 of Patent Document 8, by using the wheat bran-derived cellulose nanocrystals of the present invention instead of the cotton-derived cellulose nanocrystals, it is possible to produce a nanocomposite fiber that has excellent strength and elastic modulus, and also has excellent dyeability due to its high fiber transparency. [Industrial Applicability]

[0060] The polymer composition of the present invention can be molded by known molding methods such as injection molding and blow molding, which are used in molding polymers, in addition to the sheets and films obtained by cast molding described above. Therefore, the polymer composition can be expected to be used in a wide range of fields, not only as the sheets and films described above, but also as various molded products such as housings for electrical appliances, communication devices, printing devices, copiers, etc., and parts for automobiles, ships, etc. In addition, the fiber of the present invention is made from wheat bran, which is easily and abundantly available in Japan, and is lightweight and flexible, exhibiting excellent performance with strength equal to or greater than that of fibers made from cotton-derived nanocellulose. It also has excellent transparency and therefore good dyeability, and is expected to be used as a fiber material not only for household purposes such as clothing and interior decoration, but also for various industrial applications.

Claims

1. A polymer composition containing wheat bran-derived cellulose nanocrystals, The wheat bran-derived cellulose nanocrystals have an average diameter of 2 to 100 nm, an average length of 100 to 2000 nm, and a carboxyl group content of 30 to 2000 μmol / g, as measured by observing the morphology of the nanocrystals without dyeing using a transmission electron microscope at a voltage of 80 kV. Contains 2.5 to 10% by mass of cellulose nanocrystals derived from wheat bran. Polymer composition.

2. The polymer composition of claim 1 , wherein the polymer is a thermoplastic resin.

3. A molded article of the polymer composition according to claim 1 or 2.

4. 4. The molded article according to claim 3, which is a sheet or a film.

5. (1) A step of preparing wheat bran-derived cellulose nanocrystals by subjecting wheat bran to sulfuric acid hydrolysis; (2) mixing wheat bran-derived cellulose nanocrystals with a polymer; and (3) molding the resulting mixture; Including, A method for producing the molded article according to claim 3 or 4.

6. A fiber comprising wheat bran-derived cellulose nanocrystals, The wheat bran-derived cellulose nanocrystals have an average diameter of 2 to 100 nm, an average length of 100 to 2000 nm, and a carboxyl group content of 30 to 2000 μmol / g, as measured by observing the morphology of the nanocrystals without dyeing using a transmission electron microscope at a voltage of 80 kV. Contains cellulose nanocrystals derived from wheat bran as well as other polymers. Other polymers include nanocellulose derived from chitin from crab shells and nanocellulose derived from sea squirts. , and one or more selected from cotton-derived nanocellulose; fiber.

7. (1) A step of preparing wheat bran-derived cellulose nanocrystals by subjecting wheat bran to sulfuric acid hydrolysis; (2) Dispersing wheat bran-derived cellulose nanocrystals in a solvent; and (3) spinning the resulting mixture; Including, A method for producing the fiber of claim 6.

8. Dispersing wheat bran-derived cellulose nanocrystals in a solvent to prepare a spinning dope; and forming fibers from the resulting spinning dope; The method according to claim 7, wherein the spinning dope contains 1 to 10% by mass of wheat bran-derived cellulose nanocrystals.

9. A step of dispersing and mixing wheat bran-derived cellulose nanocrystals and a polymer in a solvent to prepare a spinning dope; and forming fibers from the resulting spinning dope; The method according to claim 8, wherein the spinning dope contains 1 to 10% by mass of wheat bran-derived cellulose nanocrystals.

Citation Information

Patent Citations

  • Short fiber food waste residue-based nano cellulose and preparation method thereof

    CN102182089A

  • Resin composition

    JP2009197122A

  • Solvent for dissolving cellulose and molded article from cellulose solution

    JP2009203467A

  • Polyvinyl alcohol-based composite fiber and method for producing the same

    JP2011208293A

  • Method for producing cellulose fibers and the fibers obtained thereby

    JP2013525618A